2016
DOI: 10.1080/19012276.2016.1162107
|View full text |Cite
|
Sign up to set email alerts
|

Parental reflective functioning in fathers who use intimate partner violence: Findings from a Norwegian clinical sample

Abstract: Few studies have examined fathering in an intimate partner violence (IPV) context outside the US. The present study included 36 Norwegian men who were voluntarily participating in therapy after perpetrating acts of IPV. They were interviewed with the revised Parent Development Interview, which is designed to assess parental reflective functioning (parental RF), and screened for alcohol- and substance-use habits and trauma history. At the group level, participants exhibited poor parental RF, high relational tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
0
15
1
2
Order By: Relevance
“…With regard to sex differences, the results indicate that fathers in our sample possessed better RF abilities and also showed more sensitive autonomy support than mothers. This result was unexpected aswith the exception of two studies where no differences were found (Borelli et al, 2017;Steele & Steele, 2008) there is evidence for lower levels of RF in men than in women (Cooke et al, 2017;Esbjørn et al, 2013;Mohaupt & Duckert, 2016;Stover & Kiselica, 2014). Nevertheless, the results were no longer significant when comparing maternal and paternal RF in families where both parents participated (i.e., excluding 14 divorced mothers).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…With regard to sex differences, the results indicate that fathers in our sample possessed better RF abilities and also showed more sensitive autonomy support than mothers. This result was unexpected aswith the exception of two studies where no differences were found (Borelli et al, 2017;Steele & Steele, 2008) there is evidence for lower levels of RF in men than in women (Cooke et al, 2017;Esbjørn et al, 2013;Mohaupt & Duckert, 2016;Stover & Kiselica, 2014). Nevertheless, the results were no longer significant when comparing maternal and paternal RF in families where both parents participated (i.e., excluding 14 divorced mothers).…”
Section: Discussionmentioning
confidence: 91%
“…Another study found that high levels of paternal RF were positively related to higher levels of social competence and RF in their adolescent children (Benbassat & Priel, 2012). Some studies showed lower levels of RF in fathers than mothers (Cooke et al, 2017; Esbjørn et al, 2013; Mohaupt & Duckert, 2016; Stover & Kiselica, 2014), but there is also a report of no such differences (Borelli et al, 2017; Steele & Steele, 2008). In one study (Borelli et al, 2016) an insufficient number of fathers participated to come to any conclusions.…”
Section: Parental Reflective Functioningmentioning
confidence: 99%
“…We assessed types and scope of violence toward partner and children from the intake interviews and referrals, parental reflective functioning (Parent Development Interview-R2; Slade et al 2003), alcohol use (AUDIT; Babor et al 2001), substance use (DUDIT; Berman et al 2007), and trauma history (TEC; Nijenhuis et al 2002). The findings and procedures from the quantitative strand of our study have been presented in a separate publication (Mohaupt and Duckert 2016).…”
Section: Methodsmentioning
confidence: 99%
“…To enhance therapeutic interventions with partner-abusive men who are fathers, we need to broaden our understanding of their everyday-life experience of being a parent. Based on our literature review and on our previous findings (Mohaupt and Duckert 2016) we knew that men who use IPV tend to score poorly on measures of parental reflective functioning. These findings indicate that they had simplistic representations of their children's mental process such as intentions, feelings and beliefs.…”
mentioning
confidence: 99%
“…I tidlige utkast har forelder ofte få eller ingen konkrete refleksjoner om og verktøy for hvordan de skal møte barna i situasjoner der de tidligere utøvde vold. Slik så første utkast ut: «Jeg kommer aldri til å slå dere igjen.» Å øke relasjons-og foreldrekompetansen er viktig i voldsspesifikk terapi, det er ikke nok å utelukkende stoppe volden (Mohaupt & Duckert, 2016).…”
Section: Del 4: Trygghetsplanunclassified